Biomarker for early prediction of cardiovascular disease (CVD) of diabetic patient and application thereof - YU MENG; ZOU ZHONGMEI; JIA HONGMEI; HE SIYAO; CHEN YANYAN; QIAN XIN (2023)
The invention relates to a kit for predicting whether a subject suffers from a cardiovascular disease, especially a cardiovascular event, and application of a reagent for determining the level of a biomarker in a biological sample in preparation of the kit. The biomarkers of the present application may be used to predict the risk of cardiovascular diseases, particularly cardiovascular events (e.g., acute myocardial infarction, acute heart failure, acute cerebral infarction, and sudden death), in a subject (e.g., a subject suffering from diabetes). 本申请涉及一种用于预测受试者是否患心血管疾病，尤其是心血管事件的试剂盒，以及用于确定生物样品中生物标志物水平的试剂在制备试剂盒中的用途。本申请的生物标志物可用于预测受试者(例如，患有糖尿病的受试者)的心血管疾病，尤其是心血管事件(例如，急性心肌梗死、急性心力衰竭、急性脑梗死和猝死)风险。